Description of Uremic Pruritus in Chronic Kidney Failure Patients Undergoing Hemodialysis at Prof. Dr. Aloei Saboe Regional General Hospital - Moh Ikbal Lahabu; Vivien Novarina A. Kasim; Maryadi Maryadi; Nurdiana Djamaluddin; Erwin Purwanto (Fakultas Kedokteran Universitas Jenderal Soedirman, 2026)
Chronic kidney disease (CKD) is a global health problem with a steadily increasing prevalence, particularly among patients undergoing hemodialysis. One of the most frequently reported complaints is uremic pruritus, defined as a chronic itching sensation that significantly affects patients' quality of life. This study aimed to describe the characteristics of uremic pruritus in patients with chronic kidney disease undergoing hemodialysis at RSUD (Regional General Hospital) Prof. Dr. Aloei Saboe, Gorontalo City. This study employed a descriptive quantitative design using a total sampling technique involving 42 CKD patients undergoing hemodialysis who presented with uremic pruritus. Data were collected using a demographic questionnaire and the 5D Itch Scale instrument. The results showed that 3 respondents (7%) experienced mild pruritus, 24 respondents (57%) experienced moderate pruritus, and 15 respondents (36%) experienced severe pruritus. The findings indicate that uremic pruritus remains a predominant clinical problem among CKD patients undergoing hemodialysis. Consequently, increased attention to assessment and management is necessary to improve patients' quality of life